Single dose systemic acetaminophen to improve patient reported quality of recovery after ambulatory segmental mastectomy: A prospective, randomized, double‐blinded, placebo controlled, clinical trial - Oliveira, Gildasio S.; Rodes, Meghan E.; Bialek, Jane; Kendall, Mark C.; McCarthy, Robert J. (The breast journal, 2018)
Few systemic drug interventions are efficacious to improve patient reported quality of recovery after ambulatory surgery. We aimed to evaluate whether a single dose systemic acetaminophen improve quality of recovery in female patients undergoing ambulatory breast surgery. We hypothesized that patients receiving a single dose systemic acetaminophen at the end of the surgical procedure would have a better global quality of postsurgical recovery compared to the ones receiving saline. The study was a prospective randomized double blinded, placebo controlled, clinical trial. Healthy female subjects were randomized to receive 1 g single dose systemic acetaminophen at the end of the surgery or the same volume of saline. The primary outcome was the Quality of Recovery 40 (QOR‐40) questionnaire at 24 hours after surgery. Other data collected included opioid consumption and pain scores. Data were analyzed using group t tests and the Wilcoxon exact test. The association between opioid consumption and quality of recovery was evaluated using Spearman rho. P < .05 was used to reject the null hypothesis for the primary outcome. Seventy subjects were randomized and sixty‐five completed the study. Patients' baseline characteristics and surgical factors were similar between the study groups. There was a clinically significant difference in the global QoR‐40 scores between the acetaminophen and the saline groups, median (IQR) of 189 (183 to 194) and 183 (175 to 190), respectively, P = .01. In addition, there was an inverse relationship (Spearman's rho= ‐0.33) between oral opioid consumption at home (oral morphine equivalents) and 24 hour postoperative quality of recovery, P = .007. A single dose of systemic acetaminophen improves patient reported quality of recovery after ambulatory breast surgery. The use of systemic acetaminophen is an efficacious strategy to improve patient perceived quality of postsurgical recovery and analgesic outcomes after hospital discharge for ambulatory breast surgery.